A critical review of blockchain-based authentication techniques - Neeraj; Anita Singhrova (The Scientific Temper, 2025)
Technology is very agile when it comes to securing data integrity, privacy and identity generally, and by extension, technology is very fit for use in the authentication of users and as a device. The focus of this paper lies in an attempt to find alternatives to the authentication in the blockchain, which is based on tokens, biometrics or knowledge. Further, the paper reviews the use of public, private and consortium blockchain in the field of healthcare, IoT, and cloud services. In this review, I will be looking at how strong blockchain-based authentication is compared with the old-school centralized authentication. It covers the advantages to security of decentralizing, but also practical limitations. Next, the challenges of scaling, spending energy, and compliance with legal regulations of blockchain in secure authentication are elaborated and the ways of improvement for blockchain in secure authentication are suggested. It provides a descriptive analysis of blockchain technologies that were recently published and a case study to compare and contrast different blockchain technologies and their usage in authenticating. This is not a systematic review as it does not discuss concepts from one perspective but rather discusses a handful of studies that contain peer-reviewed sources and evaluates the conceptual models and then accordingly assesses their performance in the real world. It offers the advantage of using different blockchain-based authentication instead of centralized systems. It eliminates single points of failure, has light tamper-proof reach back audit trials and controls personal data. The technology itself is still not close to solving those issues, which makes things too costly and too energy consuming, unable to scale and there is little point in the framework of legs. To broaden adoption for future systems, they must be more lightweight and more efficient in consensus protocols and further aligned with regulation.